Occurrence of extended- spectrum β-lactamase harboring K. pneumoniae in various sources: a one health perspective - Yasmeen, Nafeesa; Aslam, Bilal; Fang, Liang-xing; Baloch, Zulqarnain; Liu, Yahong (Frontiers in Cellular and Infection Microbiology, 2023)
This study was designed to investigate the occurrence and dissemination of extended-spectrum β-lactamase (ESBL) harboring Klebsiella pneumoniae in various ecological niches under the one health approach. A total of 793 samples were collected from animals, humans, and the environment. The findings of the study revealed the occurrence of K. pneumoniae as follows: animals (11.6%), humans (8.4%), and associated environments (7.0%), respectively. A high occurrence rate of ESBL genes was found in animals compared to human and environmental isolates. A total of 18 distinct sequence types (STs) and 12 clonal complexes of K. pneumoniae were observed. Overall, six STs of K. pneumoniae were identified in commercial chickens, and three were found in rural poultry. The majority of K. pneumoniae STs found in this study were positive for blaSHV, while the positivity of other ESBL-encoding genes combinations was different in different STs. The high occurrence rate of ESBL-harboring K. pneumoniae found in animals as compared to other sources is alarming and has the potential to be disseminated to the associated environment and community.